The Effect of Social Risk, Intellectual Capital, and HR Policies on ESG Performance of Financial Technology Companies in West Java - Nurhayadi, Willy; Fitriani, Heny; Putri, Rezty Arizta; jamaludin, Nur; Sucihati, Sucihati (Westscience Press, 2025)
This study investigates the influence of Human Resource (HR) Policies, Intellectual Capital, and Social Risk on Environmental, Social, and Governance (ESG) Performance within the fintech industry. As ESG factors increasingly shape stakeholder expectations and regulatory frameworks, fintech companies must adopt sustainable practices not only through technology but also through strategic human and intellectual resource management. Using a quantitative approach with data analyzed via Structural Equation Modeling–Partial Least Squares (SEM-PLS), the findings demonstrate that all three variables—HR Policies, Intellectual Capital, and Social Risk—positively and significantly affect ESG Performance. HR Policies emerged as the most influential factor, followed by Social Risk and Intellectual Capital. The model also shows strong explanatory and predictive relevance. These results highlight the crucial role of human capital development and risk mitigation in driving sustainability efforts in fintech firms.